Geoscience after IT : a view of the present and future impact of information technology on geoscience - Loudon, T. V. (Computer methods in the geosciences, 2000)
Most geoscientists are aware of recent IT developments, but cannot spend time on obscure technicalities. Few have considered their implications for the science as a whole. Yet the information industry is moving fast: electronic delivery of hyperlinked multimedia; standards to support interdisciplinary and geographic integration; new models to represent and visualize our concepts, and control and manage our activities; plummeting costs that force the pace. To stay on course, the scientist needs a broad appreciation of the complex and profound interactions of geoscience and IT, not previously reviewed in a single work. The book brings together ideas from many sources, some probably unfamiliar, that bear on the geoscience information system. It encourages readers to give thought to areas that, for various reasons, they have taken for granted, and to take a view on forces affecting geoscience, the consequences for themselves and their organisations, and the need to reconsider, adapt and rebuild. Practicing geoscientists with a general interest in how IT will affect their work and influence future directions of the science; geoscientists familiar with IT applications in their own specialist field who need a broader perspective; and students or educators specializing in IT applications in geoscience who require a top-down overview of their subject will find this title valuable. The IT background from this book should help geoscientists build a strategy for the new century.